Status Hukum Anak di Luar Perkawinan dalam Hukum Islam dan Implementasinya dalam Perkembangan Peraturan Perundang-Undangan di Indonesia (Studi Tentang Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010) - Sabilal Rosyad (Jurnal Hukum Islam, 2017)
This study discusses legal status –viewed in Islamic law- of a child born outside of legitimate marriage and its implementation in the development of Indonesian legislation (Study of Constitution Court Decree No. 46/PUU-VIII/2010). This research focuses on questioning a problematic decree of Constitution Court No. No. 46/PUU- VIII/2010 on legal status of a child born outside of legitimate marriage in a pluralistic Indonesian legal system. This study offers a breakthrough in responding to Constitution Court decree on a controversial legal status of a child born outside of legitimate marriage. Despite the decree, a protection of the child’s civil rights is still a grey area. This is caused by the fact that Indonesian legal system has not put a definite ruling to regulate a legal status of the child especially in granting him/her an equal civil right as a child to his/her biological father.